2011
DOI: 10.1186/1471-2407-11-9
|View full text |Cite
|
Sign up to set email alerts
|

A human ribonuclease induces apoptosis associated with p21WAF1/CIP1induction and JNK inactivation

Abstract: BackgroundRibonucleases are promising agents for use in anticancer therapy. Among the different ribonucleases described to be cytotoxic, a paradigmatic example is onconase which manifests cytotoxic and cytostatic effects, presents synergism with several kinds of anticancer drugs and is currently in phase II/III of its clinical trial as an anticancer drug against different types of cancer. The mechanism of cytotoxicity of PE5, a variant of human pancreatic ribonuclease carrying a nuclear localization signal, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 51 publications
6
43
0
Order By: Relevance
“…Here, our data showed that RNase MC2 selectively induced cell death in MCF-7 cells by virtue of its cytostatic and cytotoxic activities. This finding is reminiscent of the observation of Castro and colleagues that both onconase and PE5 possess cytostatic and cytotoxic activities [9]. Our further investigation disclosed that RNase MC2 could induce tumor cell apoptosis as exemplified by the appearance of stereotypic apoptotic features, including karyorrhexis, chromatin condensation, and DNA fragmentation (Fig.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…Here, our data showed that RNase MC2 selectively induced cell death in MCF-7 cells by virtue of its cytostatic and cytotoxic activities. This finding is reminiscent of the observation of Castro and colleagues that both onconase and PE5 possess cytostatic and cytotoxic activities [9]. Our further investigation disclosed that RNase MC2 could induce tumor cell apoptosis as exemplified by the appearance of stereotypic apoptotic features, including karyorrhexis, chromatin condensation, and DNA fragmentation (Fig.…”
Section: Discussionsupporting
confidence: 49%
“…After incubation for 24 h, the cells were treated with increasing concentrations (0, 0.195 to 25 lM) of RNase MC2 for 24-48 h, and cell viability was determined by MTT assay [13]. In addition, total cell numbers as well as cell death in different group were counted using a haemocytometer combined with the trypan blue exclusion assay [9]. SPSS 11.0 software was used for IC 50 analysis.…”
Section: Assays Of Ribonucleolytic Activity and Base-specificitymentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, Onconase has been used as an antitumor agent in clinical trials (7,19,25). Additionally, a previous study reported that Onconase exerts a cytotoxic effect on the human glioma SHG-44 cell line (26).…”
Section: Introductionmentioning
confidence: 99%